2020
DOI: 10.3389/fpubh.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Stand for Office-Based Workers' Mental Health: The Return of the Microbreak

Abstract: There is evidence that movement-based microbreaks can improve the cardiovascular health of desk-based employees, but their effect on mood states is yet to be investigated. As daily work tasks can potentially result in the loss of physical and psychological resources, the objective of this study was to measure the effect of movement microbreaks during formal work time on mood states. In a randomized-controlled pilot study with repeated measures (baseline, post-test, washout) of self-reported job stress and mood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…However, active workstations are not without their acceptability and feasibility issues, which potentially limits their use [ 24 , 31 ]. Free-living physical activity modalities such as walking breaks have received encouraging success in breaking up sitting time and improving both cardiovascular biomarkers [ 41 , 59 , 60 ]. Therefore, through co-producing a free-living physical activity intervention, we aimed to overcome these potential barriers whilst incorporating the stakeholders within the design and delivery of the intervention, and senior management support to create appropriate social norms within the employment setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, active workstations are not without their acceptability and feasibility issues, which potentially limits their use [ 24 , 31 ]. Free-living physical activity modalities such as walking breaks have received encouraging success in breaking up sitting time and improving both cardiovascular biomarkers [ 41 , 59 , 60 ]. Therefore, through co-producing a free-living physical activity intervention, we aimed to overcome these potential barriers whilst incorporating the stakeholders within the design and delivery of the intervention, and senior management support to create appropriate social norms within the employment setting.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace prompting software (e.g., Exertime TM ) may provide a suitable prevention strategy for desk-based employees to improve their physical health (e.g., decreased blood pressure [ 11 ]), and mental health [ 12 ]. Putatively, these health improvements are caused by the Exertime TM prompts changing a person’s desk-based behavior, i.e., the amount and pattern of sedentary behavior and movement while in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Though poor mental health is linked with the sickness absenteeism and low workability in desk-based office workers, the empirical evidence designed to prove the relations remains mixed (Qi et al, 2019;Ryde et al, 2019). Epidemiological and observational studies have found a significant relation between the physical health variables (sit-stand transitions, sitting time during workday and non-workday and micro-breaks) and the mental health variables (perceived stress, anxiety and depression) (Mainsbridge et al, 2020;Qi et al, 2019;Ryde et al, 2019). However, there is still a lack of cost-effective interventions to address the physical and psychological effects of teleworking (Ford et al, 2020;Rehman et al, 2020;Tan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%